تأثير التعلم العملي في تحسين مهارات الطلاب في التحدث باللغة العربية: الجامعة الإسلامية العالمية بماليزيا أنموذجا = The impact of practical learning on improving students' Arabic speaking skills- The International Islamic University Malaysia as a case study - Chtaibi, Khalid; Nasirudeen, Abdulwasiu Isiaq; Marjuskai, Farihin Mufeed (Faculty of Languages at Al-Madinah International University, 2026)
يتناول البحث استكشاف تأثير التعلم العملي في تطوير مهارات الطلاب اللغوية وقدراتهم اللغوية أثناء دراستهم اللغة العربية، بما يتجاوز الجوانب النظرية. واستخدمت الدراسة المنهج الكمي، باستخدام استبيان شارك فيه 50 طالبا وطالبة يدرسون اللغة العربية للتواصل العالمي في الجامعة الإسلامية العالمية بماليزيا. وقد أشار معظم المشاركين في الدراسة إلى أن التعلم العملي يسهل تعزيز كفاءتهم التواصلية؛ حيث أظهرت النتائج أن الطلاب الذين تخصصوا في اللغة العربية للتواصل الدولي أكدوا أن التعلم العملي ساعدهم على تنمية مواهبهم ومهاراتهم في اللغة العربية، على أساس أن اكتساب المهارات من خلال التعلم العملي له أثر إيجابي واضح في إتقان المحادثة خاصة في مجالي وضوح الأفكار والتواصل الاستراتيجي. وأخيرا، يمثل التعلم العملي منهجا مكملا للتعليم التقليدي؛ حيث يكمل المعرفة النظرية بالخبرة العملية بشكل فعال لتعزيز تنمية مواهب ومهارات التحدث. ***** The article contributes to the understanding of the practical learning process in developing students’ linguistic skills and abilities when they embark upon the study of the Arabic language. This research aims to identify the impact of practical learning and to determine the benefits of studying Arabic beyond the theoretical aspects. The study employed a quantitative methodology, utilizing a questionnaire completed by 50 students pursuing Arabic for international communication in Kulliyyah of Sustainable Tourism and Contemporary Languages. Most respondents indicated that practical learning facilitates the enhancement of their oral proficiency. In their own learning style, the students apply themselves to the development of their speaking abilities and skills in the Arabic language. Practical learning within the context of the Arabic course cannot facilitate the understanding of Arabic native speaker language for those who have not yet acquired sufficient fluency, particularly in the case of beginners. The result from this research showed that students who majored in Arabic for international communication indicated that practical learning helped them develop their talents and skills in the Arabic language, acquiring skills through practical learning has a clear positive impact on mastering verbal communication, especially in the areas of clarity of ideas and strategic communication and lastly, practical learning represents a complementary approach to traditional education, effectively complementing theoretical knowledge with practical experience to enhance the development of speaking talents and skills